The effectiveness of using some teaching syles based on the knowledge economy to achieve some curriculum outcomes in the psychomotor domain for students (12-13) years old - حياة بن كرداغ; حبيب بن سي قدور; بن قاصد علي حاج محمد (Journal of Sport Science Technology and Physical Activities, 2026)
Previous studies have concluded that the traditional teaching model does not take into account individual differences between students, their needs, problem-solving skills, and cooperative learning abilities.Accordingly, the study aimed to determine the effectiveness of integrating cooperative learning and problem-solving styles in light of the requirements of the knowledge economy on some curriculum outcomes in the psychomotor field, in order to ensure active learning that provides opportunities for distinguished qualitative education and creative and interactive work for students. The experimental approach was used to design two groups of 15 students each. After statistical treatment, the differences were significant in favor of the experimental sample, and therefore the study recommended working with a model of integrating cooperative learning and problem-solving styles as an indicator of the knowledge economy for effectiveness in improving offensive skills and problem-solving efficiency (fluency, originality, flexibility) among students in Basketball